(untitled) (Bangladesh Journal of Medical Science, 2014)
Background: In Bangladesh, prevalence of kidney diseases is increasing day by day and it was observed that renal medulla is affected less in earlier period of life but in late period it becomes affected more. Moreover renal mass changes with age which affecting the medullary mass and consequently the number of medullary pyramids. So the present study was carried out to evaluate anatomical features of medulla and to count the medullary pyramids with age related changes in the number of the pyramids in Bangladeshi people. Study type: Cross sectional analytical type of study. Place and period of study: Department of Anatomy, Mymensingh Medical College, Mymensingh, Bangladesh from January 2004 to June 2005. Materials and methods: A total of 70 fresh human kidneys of both sexes and sides were collected from the morgue of Mymensingh Medical College at postmortem. The selected cases were between 5 to 60 years of age. The samples were divided into 3 different age groups (A: 05-15 years, B: 16-35 years, C: 36- 60 years) to observe the variations in number of medullary pyramid of kidney in different age groups. Results: Among three groups, highly significant (<0.001) differences were found statistically in the number of medullary pyramid. Conclusion: There were changes in the number of medullary pyramid of kidney in different age groups. DOI: http://dx.doi.org/10.3329/bjms.v13i2.18299 Bangladesh Journal of Medical Science Vol.13(2) 2014 p.155-157